Endophytic microorganisms for biocontrol of the phytopathogenic fungus Botrytis cinerea (2019)
Botrytis cinerea is the most widely studied necrotrophic phytopathogenic fungus. It causes economic losses that are difficult to calculate due to the large number of hosts. While there are a wide array of fungicides on the market to control this phytopathogen, they are not considered sustainable in terms of the environment and human health. The search for new alternatives to control this phytopathogen has led to the use of endophytic microorganisms as biological control agents. Endophytic bacteria and endophytic fungi have been isolated from different plant species and some have proven effective in inhibiting B. cinerea. Furthermore, a significant number of fungistatic or fungicidal metabolites which could be used as alternative complementary chemical controls have been isolated from these fungi and bacteria. In this review, in addition to the metabolites which have shown fungicide activity against this phytopathogen, the different genera and species of endophytic bacteria and fungi are also considered. These have been isolated from various plant species and have displayed antagonistic activity against B. cinerea.